The Internal Market at a Social Turn? Social dumping and the protection of workers. Issue 4 (December 2020) - Jacqueson, Catherine
Free movement should in theory enable individuals to fight poverty at home by finding employment in another Member State. Yet, free movement is not always that easy and can in practice lead to social dumping in specific sectors where posted workers ultimately push salaries to the bottom. Such a race to the bottom might also arise outside a free movement context when workers are falsely qualified as self-employed thus undercutting wages. This article argues that EU economic law both creates risks of social dumping and remedies them. It calls for a rebalancing of the liberal ethos of the principle of free movement and competition law on the one hand, and the social objectives of the EU, on the other hand. A key question is whether it is possible to redress the balance between the economic and the social from within the internal market logic or whether the social push has to come from outside.